If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -18 = 39x + 19 Reorder the terms: -18 + 8x = 39x + 19 Reorder the terms: -18 + 8x = 19 + 39x Solving -18 + 8x = 19 + 39x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39x' to each side of the equation. -18 + 8x + -39x = 19 + 39x + -39x Combine like terms: 8x + -39x = -31x -18 + -31x = 19 + 39x + -39x Combine like terms: 39x + -39x = 0 -18 + -31x = 19 + 0 -18 + -31x = 19 Add '18' to each side of the equation. -18 + 18 + -31x = 19 + 18 Combine like terms: -18 + 18 = 0 0 + -31x = 19 + 18 -31x = 19 + 18 Combine like terms: 19 + 18 = 37 -31x = 37 Divide each side by '-31'. x = -1.193548387 Simplifying x = -1.193548387
| logx-1(4x-4)=2 | | t^2+13t=0 | | 4e^3x-2=244 | | 7(n+6)=98 | | 2(6x-7)=-39+7x | | 105=-7(x-8) | | -9-4x=-6x-19 | | 0.8x-1.8=3.9x+1.9 | | 6(1-4m)=-90 | | 5(2+2x)=4(3-3x) | | (4n-7)(8n-7)= | | 17=1+4p | | cos(3x+20)=0.2 | | 240=12x | | ab=9 | | 1=4+p | | 8x^2-12y+4=y+10 | | cos(3o+20)=0.2 | | 4+3x+6=4x-5 | | x+(-10)=-22 | | 27-7r=-(1+3r) | | 20+2p=8+6(-8+2p) | | -5(a+6)=-14-7a | | 2y^2+14=104 | | x(5)=-5-1 | | 2(x+6)=3(x+4)+5 | | 180(n-1)=900 | | -84=7(p-4) | | -105=-7(1-2r) | | -75-18v=-70 | | =9p^5q+6p^4-15p^2q^4 | | -84=6(n-7) |